2016
DOI: 10.1007/s12262-015-1439-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing Risk Prediction Models for Postoperative Pancreatic Fistula: a Systematic Review of Methodology and Reporting Quality

Abstract: Postoperative pancreatic fistula is still a major complication after pancreatic surgery, despite improvements of surgical technique and perioperative management. We sought to systematically review and critically access the conduct and reporting of methods used to develop risk prediction models for predicting postoperative pancreatic fistula. We conducted a systematic search of PubMed and EMBASE databases to identify articles published before January 1, 2015, which described the development of models to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Our main finding of inadequate reporting in the majority of publications within 37 clinical domains is comparable to the findings of systematic reviews of prediction model studies performed in general medicine or specific clinical domains [ 6 11 ]. Inadequate reporting is considered to be a form of research waste [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our main finding of inadequate reporting in the majority of publications within 37 clinical domains is comparable to the findings of systematic reviews of prediction model studies performed in general medicine or specific clinical domains [ 6 11 ]. Inadequate reporting is considered to be a form of research waste [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 81%
“…Previous systematic reviews showed that within different clinical domains the quality of reporting of prediction models is suboptimal [ 6 11 ]. To improve the reporting of studies of prediction models, a guideline for the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) was launched in January 2015 in more than 10 medical journals [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current analysis, where we observed a median adherence of 42% (LQ-UQ: 31 to 57%) amongst published articles, were in line with findings from an earlier study by Heus et al [4] which reported a median adherence of 44% (LQ-UQ: 35 to 52) in 170 models across 37 clinical domains, in articles published prior to the publishing of the TRIPOD statement. Since the introduction of the TRIPOD statement [2,3], continued poor reporting has been observed [21][22][23], with the present analysis suggesting that current reporting quality in the field of COVID-19 prediction is no different to the situation prior to publication of the TRIPOD statement. This is likely due to the less rigorous peer review and editorial process for COVID-19 articles during the pandemic.…”
Section: Comparison To Other Studiesmentioning
confidence: 60%
“…Attention should be paid to the pathology of POPF. It has been reported that pancreatic fistula may be related to following aspects: 22 24 (1) When tissue and tissue are anastomosed, the needle passes through the pancreatic tissue and may break through the expanded small pancreatic duct, which may also cause pinhole infiltration, thereby causing leakage of pancreatic juice; (2) When the pancreas and intestine are anastomosed, there must be a gap between the needles, which causes pancreatic juice to leak out from the gap; (3) There is high pressure in the jejunal intestine tube. At the end of surgery, if the intestines cannot work normally and peristalsis is weak, and there is a long jejunal bridge after co-operating with the pancreas, this can easily cause pancreatic juice and bile retention in the intestine.…”
Section: Discussionmentioning
confidence: 99%